Domain decomposition parallel multilevel methods for elliptic partial differential equations - Smith, Barry F.; Bjørstad, Petter E.; Gropp, William 1955- (Cambridge Univ. Press, 2004)
An easy-to-read discussion of domain decomposition algorithms, their implementation and analysis.
Keywords: Ayrıştırma metodu - Bilgi işlem; Diferensiyel denklemler, Eliptik - Sayısal çözümler - Bilgi işlem; Paralel işlem (Elektronik bilgisayarlar); Datenverarbeitung; Decomposition method -- Data processing; Differential equations, Elliptic -- Numerical solutions -- Data processing; Parallel processing (Electronic computers); Gebietszerlegungsmethode; Elliptische Differentialgleichung